2021
DOI: 10.3390/ijms23010092
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MAPK/NF-κB Pathways in Anti-Inflammatory Potential of Rutaecarpine: Impact on Src/FAK-Mediated Macrophage Migration

Abstract: Studies have discovered that different extracts of Evodia rutaecarpa and its phytochemicals show a variety of biological activities associated with inflammation. Although rutaecarpine, an alkaloid isolated from the unripe fruit of E. rutaecarpa, has been exposed to have anti-inflammatory properties, the mechanism of action has not been well studied. Thus, this study investigated the molecular mechanisms of rutaecarpine (RUT) in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages. RUT reserved the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…MAPK pathways, such as ERK 1/2, p38 kinase, JNK, and NF-κB pathways, are known to be common inflammatory signaling pathways that cause the release of proinflammatory cytokines, such as IL-1β, and consequently lead to inflammation ( Jayakumar et al, 2021 ). Therefore, the activation of MAPK and NF-κB was assessed in RAW 264.7 cells pretreated with or without gDNAs.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK pathways, such as ERK 1/2, p38 kinase, JNK, and NF-κB pathways, are known to be common inflammatory signaling pathways that cause the release of proinflammatory cytokines, such as IL-1β, and consequently lead to inflammation ( Jayakumar et al, 2021 ). Therefore, the activation of MAPK and NF-κB was assessed in RAW 264.7 cells pretreated with or without gDNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies from our group have proven the antiplatelet mechanisms of Rut through suppressing phosphoinositide 3-kinase (PI3K)/Akt/MAPK [ 23 ], p38-mediated NF-κB activation [ 24 ], and PI3K/Akt/glycogen synthase kinase-3β (GSK3β) [ 23 ] signaling cascades. Another relevant study found that Rut diminishes LPS-induced migration by hindering the Src/FAK pathway [ 25 ]. In this study, we demonstrated that Rut inhibits inflammatory molecules including NO production, iNOS, COX-2, and IL-1β expression in LTA, a Gram-positive bacterial cell wall component, induced RAW cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory proteins are regulated by the MAPK and NF-κB pathways. Several natural products from plant extracts regulate inflammatory proteins through regulation of the MAPK and NF-κB signaling pathways (Jayakumar et al 2021;Chauhan et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NF-κB can be activated via mitogen-activated protein kinases (MAPKs), such as c-Jun NH 2 -terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38, which are regulated by mitogen-activated protein kinase (MEK) (Hoesel et al 2013). It has been reported that various natural compounds derived from medicinal plants are effective in the treatment of inflammatory diseases through regulation of the related signaling pathways (Jayakumar et al 2021;Chauhan et al 2022).…”
Section: Introductionmentioning
confidence: 99%